Many faces of osteosarcoma on plain radiographs. Issue 1 (29th August 2014) - Clayer, Mark
Abstract Osteosarcoma is the most common primary malignancy of bone. It is a very rare form of cancer with an annual incidence of 3:1 000 000 and so will not be seen by many surgeons. Coupled with this are the many different subtypes of this cancer that can have different appearances on imaging ranging from densely sclerotic to lytic or even cystic. They can be medullary, cortically or periosteally based. This article demonstrates the various different appearances associated with the different types of osteosarcoma which will assist surgeons in diagnosing this rare cancer.